Evaluation of site amplification factors for shallow rock sites of Islamabad, Pakistan. - Shamsher Sadiq; Aaqib Muhammad; Saeed-ullah Jan Mandokhail; Maqsood-Ur Rehman; Alam Mehtab; Naik Muhammad; Muhammad Bilal Adeel (Kuwait Journal of Science)
Current seismic provisions in Building Code of Pakistan (BCP, 2007), seismic site classifications and corresponding site amplification factors (AF) were determined similar to UBC-1997, which were based on the local site conditions of Western United States (WUS) with low impedance contrast, deep sites and high seismicity conditions. Use of these deep sites based AF factors to the shallow sites may not be appropriate to capture the response of shallow sites. In this study, we performed suite of nonlinear site specific response analysis to compute the AF for the six (06) representative shallow bed rock sites of Islamabad, Pakistan. The computed AF are compared with BCP, 2007 code-based design estimates, it is found that BCP, 2007 code based guideline underestimate AF factor at short period whereas overestimate at long period. The findings of the study, highlights the potential implications of current code based AF for the shallow sites of Islamabad, and suggest the need of improving the current seismic guidelines.